Taxing Celebrity Social Media Endorsements Income: A Preliminary Study of Instagram Celebrities - Afrizal Tahar; Listya Maharani Rizkia; Eko Hariyanto (Universitas Muhammadiyah Yogyakarta, Indonesia, 2020)
This study investigates how tax treatment should be done for a celebrity of Instagram (Celebgram) income obtained from endorsement activities on social media. In detail, this study aims to find out how income from endorsement can be used as taxable income as well as to discover how a possible collection strategy can be executed. In addition, this study explores the perceptions of celebgrams regarding the application of tax to their endorsement income. Semi-structured interview was employed to obtain the data. Informants of the current study are tax official, tax consultants, tax academics, information technology experts, and five celebgrams. The results of this study reveal that celebgram income from endorsement can be taxable in the categories of income tax and value-added tax. The majority of the celebgrams agree if their income from endorsement would be taxed on as far as the level of fair and clear treatment. Furthermore, endorsement tax collection needs a special unit and support by a capable employee and adequate information technology.